Dampak Psikologis Tenaga Kesehatan Selama Pandemi COVID-19 - Pinggian, Brian; Opod, Henry; David, Lydia (Jurnal Biomedik : JBM, 2021)
Abstract: The Corona Virus Disease 2019 (COVID-19) outbreak that emerged in December 2019 in Wuhan, quickly spread outside of China, so the World Health Organization (WHO) declared an Emergency at the Public Health Emergency of International Concern (PHEIC), causing Psychological Stress on Health workers who handle COVID-19 patients, the purpose of this study is to determine the Psychological Disorders of Health Workers during the COVID-19 pandemic. This study is a literature review by comparing articles, journals or secondary data from previously published literature contained in the medical journal database Science Direct, PubMed and ClinicalKey. Result of the ten articles reviewed, there were 11,611 respondents consisting of 3,070 men, 8,534 women, 4 respondents who did not fill in gender and 1 Genderqueer respondent obtained data on increased psychological pressure from health workers during the COVID-19 pandemic. In conclusion, it found the prevalence of psychological impacts such as stress, anxiety and depression from mild to severe among health workers during the COVID-19 pandemic. These findings will help improve our understanding of the impact or impact of the COVID-19 pandemic on the Psychology of Health Workers.Keywords: Psychological Impacts, Health Workers, the COVID-19 Pandemic  Abstrak: Wabah Corona Virus Disease 2019 (COVID-19) yang muncul pada Desember 2019 di Wuhan, dengan cepat menyebar ke luar Tiongkok, sehingga World Health Organization (WHO) mengumumkan Darurat pada Public Health Emergency of International Concern (PHEIC), menyebabkan Tekanan Psikologis pada tenaga Kesehatan yang menangani Pasien COVID-19, tujuan dari penelitian ini untuk mengetahui Gangguan Psikologis pada Tenaga Kesehatan selama Masa pandemi COVID-19. Metode penelitian berupa literature review dengan membandingkan artikel jurnal atau data sekunder dari literatur-literatur yang dipublikasi sebelumnya  yang terdapat dalam database jurnal kedokteran Science direct, PubMed dan ClinicalKey. Hasilnya sebanyak sepuluh artikel yang direview terdapat 11.611 responden yang terdiri dari 3.070  laki-laki, 8.534 perempuan, 4 responden tidak mengisi gender dan 1 responden Genderqueer didapatkan data peningkatan tekanan Psikologis dari para tenaga Kesehatan selama masa pandemi COVID-19. Sebagai simpulan,  ditemukan prevalensi dampak psikologis seperti stres, kecemasan dan depresi dari ringan hingga Berat pada Tenaga Kesehatan selama masa pandemi COVID-19. Temuan ini akan membantu meningkatkan pemahaman kita tentang pengaruh atau dampak pandemi COVID-19 pada Psikologis Tenaga Kesehatan.Kata Kunci: Dampak Psikologis,Tenaga Kesehatan, Pandemi COVID-19